Implementing Language Policy at School: The Case of Balinese Language - Dewi, Desak Nyoman Dyah Rupita (Lingua Scientia, 2011)
The present study aimed at investigating the implementation of language policy in maintaining and promoting Balinese at school. This research was a case study which took place at Taman Rama National Plus School, Badung. The subjects of the study were selected on the basis of purposive sampling. They were four students and a teacher. In this study, the data were collected by using two instruments, namely human instrument and interview guide. The findings show that Taman Rama National Plus School has a language policy that the school staff members and students should speak Balinese on Wednesdays. However, this policy could not be applied in doing communication and teaching because of two things, namely: the majority of non-Balinese speaking students and the poor mastery of Balinese on the part of the Balinese students. This study also highlites that the role of parents has greater influence than economic status of family in introducing and habituating children to use Balinese at home.